Trajectories of Palliative Care Needs in the ICU and Long-Term Psychological Distress Symptoms*. Issue 1 (3rd November 2022) - Cox, Christopher E.; Gu, Jessie; Ashana, Deepshikha Charan; Pratt, Elias H.; Haines, Krista; Ma, Jessica; Olsen, Maren K.; Parish, Alice; Casarett, David; Al-Hegelan, Mashael S.; Naglee, Colleen; Katz, Jason N.; et al.
Abstract : OBJECTIVES: While palliative care needs are assumed to improve during ICU care, few empiric data exist on need trajectories or their impact on long-term outcomes. We aimed to describe trajectories of palliative care needs during ICU care and to determine if changes in needs over 1 week was associated with similar changes in psychological distress symptoms at 3 months. DESIGN: Prospective cohort study. SETTING: Six adult medical and surgical ICUs. PARTICIPANTS: Patients receiving mechanical ventilation for greater than or equal to 2 days and their family members. MEASUREMENTS AND MAIN RESULTS: The primary outcome was the 13-item Needs at the End-of-Life Screening Tool (NEST; total score range 0–130) completed by family members at baseline, 3, and 7 days. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Post-Traumatic Stress Scale (PTSS) were completed at baseline and 3 months. General linear models were used to estimate differences in distress symptoms by change in need (NEST improvement ≥ 10 points or not). One-hundred fifty-nine family members participated (median age, 54.0 yr [interquartile range (IQR), 44.0–63.0 yr], 125 [78.6%] female, 54 [34.0%] African American). At 7 days, 53 (33%) a serious level of overall need and 35 (22%) ranked greater than or equal to 1 individual need at the highest severity level. NEST scores improved greater than or equal to 10 points in only 47 (30%). Median NEST scores were 22 (IQR, 12–40) at baseline and 19 (IQR, 9–37) at 7 days (change, –2.0; IQR, –11.0 to 5.0; p = 0.12). There were no differences in PHQ-9, GAD-7, or PTSS change scores by change in NEST score (all p > 0.15). CONCLUSIONS: Serious palliative care needs were common and persistent among families during ICU care. Improvement in needs was not associated with less psychological distress at 3 months. Serious needs may be commonly underrecognized in current practice.